Efektivitas Penegakan Hukum terhadap Penjual Kosmetik Ilegal pada Undang-Undang Nomor 36 Tahun 2009 Tentang Kesehatan di Kota Gorontalo - Mohamad Eka Purwanto (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to find out how effective law enforcement is against illegal cosmetic sellers in Law Number 36 of 2009 concerning health in Gorontalo City and what challenges and obstacles are faced by law enforcers in dealing with illegal cosmetic sellers in Gorontalo City. This research uses empirical legal research methods which are carried out by collecting data through observation and interviews.The results of this research show that in enforcing laws related to the distribution of illegal cosmetics, law enforcement officers usually apply Law Number 36 of 2009 concerning Health and Law Number 8 of 1999 concerning Consumer Protection. Apart from that, through BPOM Regulation Number 26 of 2017 concerning the Organization and Work Procedures of BPOM, the Food and Drug Supervisory Agency (BPOM) is at the forefront of the government in fostering and monitoring distribution, quality and licensing as well as Law Enforcement factors in Handling Illegal Cosmetic Sellers in the City Gorontalo, namely legal substance, legal structure, legal culture, facilities and infrastructure, and legal knowledge of the community, need to be studied in more depth so that their influence on the challenges and obstacles in law enforcement for dangerous illegal cosmetic business actors in Gorontalo City can be known.